Wnt5a Increases the Glycolytic Rate and the Activity of the Pentose Phosphate Pathway in Cortical Neurons. (5th September 2016) - Cisternas, Pedro; Salazar, Paulina; Silva-Álvarez, Carmen; Barros, L. Felipe; Inestrosa, Nibaldo C.
Abstract : In the last few years, several reports have proposed that Wnt signaling is a general metabolic regulator, suggesting a role for this pathway in the control of metabolic flux. Wnt signaling is critical for several neuronal functions, but little is known about the correlation between this pathway and energy metabolism. The brain has a high demand for glucose, which is mainly used for energy production. Neurons use energy for highly specific processes that require a high energy level, such as maintaining the electrical potential and synthesizing neurotransmitters. Moreover, an important metabolic impairment has been described in all neurodegenerative disorders. Despite the key role of glucose metabolism in the brain, little is known about the cellular pathways involved in regulating this process. We report here that Wnt5a induces an increase in glucose uptake and glycolytic rate and an increase in the activity of the pentose phosphate pathway; the effects of Wnt5a require the intracellular generation of nitric oxide. Our data suggest that Wnt signaling stimulates neuronal glucose metabolism, an effect that could be important for the reported neuroprotective role of Wnt signaling in neurodegenerative disorders.